CREATIVITY OF GERMAN LANGUAGE TEACHERS IN LEARNING - Bisenbaeva is the daughter of Nargiza Aytbay (Journal of new century innovations, 2023)
Abstract: One of the alternative methods in the field of research aimed at preventing information fatigue and increasing students' intellectual activity is "surprise" or, in other words, "miracle effect". The system of encounters with fascinating objects, their research on their creation ensures the interest and efficiency of the activities of junior schoolchildren.